Sadd Al-Dzari'ah Dalam Menentukan Fatwa Halal Dan Haram di Lombok - Yusup, Muh; Irfan Azim (Kartika: Jurnal Studi Keislaman, 2025)
The concept of Sadd al-Dzari'ah is a fundamental principle in determining halal and haram fatwas in Islam, which aims to prevent all forms of danger (mafsadah) and maintain the welfare (maslahah) of both individuals and society. This research aims to analyze the application of the Sadd al-Dzari'ah concept in the contemporary context, especially in the fields of Islamic banking and finance, health and food products, as well as its response to the challenges of globalization, multiculturalism and socio-moral change. Using a critical literature review method, this research examines the conceptual basis, methods of legal interpretation (such as ijma', qiyas, istihsan, istishab, and maslahah murlah), as well as contemporary fatwa case studies involving Sadd al-Dzari'ah. The research results show that this concept plays a key role in ensuring the conformity of Islamic financial products and transactions with Sharia principles, assessing the halalness and safety of food and health products, and addressing modern ethical issues such as technological developments, reproductive rights, and cultural diversity. Furthermore, this study confirms that Sadd al-Dzari'ah serves as a vital instrument in maintaining the relevance, integrity, and adaptability of Islamic law amidst complex global dynamics. The implications of this research not only provide a more comprehensive guiding framework for Muslims in making daily decisions in accordance with Sharia but also make a significant contribution to the development of a sustainable, ethical, and religiously responsive Islamic finance industry.